Deep grey matter and fatigue in multiple sclerosis - Niepel, Graham (2012)
Fatigue is a common and major symptom in multiple sclerosis (MS). A number of potential mechanisms exist as to the cause of MS-fatigue. These include that it is an immune-mediated symptom or that it is due to neuroendocrine or autonomic dysfunction. Studies have shown reduced activity in cortical and deep grey matter regions and disruption of cortico-subcortical circuits has been theorised. This may lead to difficulty in the planning or pre-movement stage of activity with compensatory overactivity contributing to fatigue. Finally, dysfunction of the hypocretin system, deficiency of which occurs in narcolepsy, has also been suggested. A number of deep grey matter structures, including the basal ganglia, thalamus and hypothalamus, are implicated in these mechanisms and the work presented in this thesis explores their role.